(untitled) (World Bulletin of Management and Law, 2024)
This essay explores the main functions of current AI applications which can be used in the appointment of arbitrators or even in the case management to schedule time of conference and analyze different facts.1 Then it explains limitations of AI in the decision-making process by giving different examples. At the end it assures that AI programs cannot take over the place of human arbitrators because of some ethical concerns